Implementation Of Architecture Based Object Oriented Software System Reliability Prediction Model : Research Paper - Kashyap, Shailja; Srivastava, Durgesh (IJRDO -Journal of Computer Science Engineering, 2016)
Reliability of software system is the measure of extent to which a system can work efficiently and asexpected, subjected to certain constraints and time period .Prediction or measurement of reliability ofsoftware system have been in lime light in world of software engineering researches .Multiplemodels and measurement tools have been designed to estimated the reliability based on differentcriteria for example, some models are based on failure rate, some on complexity matrix and otherson system component failure probabilities .In this paper we introduce a system or software tool topredict object oriented software reliability at design and analysis phase .System is an implementationof already existing architecture based model , which makes use of annotated UML diagrams .Thesystem output helps the user to easily calculate various failure probabilities and at the end over allsystem reliability ,at design phase itself, so the appropriate steps could be taken at an early stage.UML diagrams are created using UMLET software and the system have been developed in CPP .